2018
DOI: 10.1088/1361-648x/aaeafd
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of ethylene with free gold cluster cations: infrared photodissociation spectroscopy combined with electronic and vibrational structure calculations

Abstract: The interaction of ethylene with free gold clusters of different sizes and charge states has been previously shown theoretically to involve two different adsorption modes of the C 2 H 4 molecule, namely: the di-and-bonded ethylene adsorption configurations. Here, we present the first experimental investigation of the structure of a series of gas-phase gold-ethylene complexes, Au x (C 2 H 4) y + (x =2-4, y =1-3). By employing infrared multiple-photon dissociation spectroscopy (IR-MPD) in conjunction with first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 61 publications
5
17
0
3
Order By: Relevance
“…The donation/back‐donation mechanism of ethylene adsorption on gold clusters was inferred from changes in the total charge of the adsorbate and the clusters bond lengths . It was shown that CO adsorption on Pd clusters elongates the Pd−Pd and C−O bonds, which supports a donation/back‐donation mechanism .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The donation/back‐donation mechanism of ethylene adsorption on gold clusters was inferred from changes in the total charge of the adsorbate and the clusters bond lengths . It was shown that CO adsorption on Pd clusters elongates the Pd−Pd and C−O bonds, which supports a donation/back‐donation mechanism .…”
Section: Introductionmentioning
confidence: 92%
“…The bond formation and bond breaking processes are confined to the catalytically active sites, which can be modelled by small clusters. [27] Beside the calculation of the reactione nergy,t he analysisa nd the understanding of the chemicali nteractions between catalyst andr eagents is important for rational catalyst design.F or cluster-adduct complexes, the changes in bond lengths and charges, [28][29][30] the frontier orbital and population analysis, [31][32][33] ionization potentials and electron affinities, [34] and NBO analysis, [35] are commonlyu sed to analyse the chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, νC−C is known to be very sensitive to the C−C bond lengths. 12 For example, for small hydrocarbons νC−C blue-shifts almost linearly from 995 cm −1 for C 2 H 6 with d(C−C) = 1.535 Å to 1623 cm −1 for C 2 H 4 with d(C = C) = 1.339 Å and 1974 cm −1 for C 2 H 2 with d(C C) = 1.203 Å. 31,32 This suggests that the blue-shift of ν s OCO + νC−C is mainly caused by a shortening of the C−C bond; the observed shift of about 30−45 cm −1 might already be caused by a change of the C−C bond length of <0.05 Å.…”
Section: Influence Of Cluster Composition On the C−cmentioning
confidence: 99%
“…65 The NO stretching frequency of AunNO + complexes exhibits marked odd-even alternation, as the unpaired electron in the l Aun + (n = even) clusters efficiently donates into the NO * orbital, efficiently activating it. 7 Infrared studies of other adsorbates (e.g., CO, 7,66 methane, 67 methanol, [68][69][70] ethanol, 71 and ethene 72 ) on gold clusters suggest alternative binding mechanisms for which odd-even size effects are less clear. All small gold clusters selectively dissociate a single C-H bond in CH4 but, whilst CH4 binding energies to Aun + show a clear size dependence, 73 this is not reflected in the IR-MPD spectra.…”
Section: Introductionmentioning
confidence: 99%